The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1109/led.2013.2258135
|View full text |Cite
|
Sign up to set email alerts
|

540-meV Hole Activation Energy for GaSb/GaAs Quantum Dot Memory Structure Using AlGaAs Barrier

Abstract: We report on a memory structure that only makes use of holes as the storage charges based on type-II GaSb/GaAs quantum dots (QDs) using an AlGaAs barrier. The C-V measurements confirm existence of quantum states in the GaSb dots and reveal the applied bias voltage range for the write/erase process by charging/discharging the QDs. A large hole activation energy value of 540 meV is obtained for the device measured by deep level transient spectroscopy. Our results indicate that type-II GaSb/GaAs QD system is a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In our previous work, we suggested a possible readout scheme for picking up this voltage change near the QD in a narrow measurement time window of picoseconds . For most of the Modes discussed in Working Modes of the Proposed SQDSPD, the output signal has a retention time equal to the trapped charge lifetime (e.g., τ 6 in Figure f), which can be as long as microseconds. , This long signal retention time helps relax significantly the tight timing requirements imposed on the readout circuit, as compared to the situation in ref . Hence, the design of the readout scheme can emphasize more on the optimization of parameters such as the amplification of the voltage signal, rather than be limited by the short readout time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous work, we suggested a possible readout scheme for picking up this voltage change near the QD in a narrow measurement time window of picoseconds . For most of the Modes discussed in Working Modes of the Proposed SQDSPD, the output signal has a retention time equal to the trapped charge lifetime (e.g., τ 6 in Figure f), which can be as long as microseconds. , This long signal retention time helps relax significantly the tight timing requirements imposed on the readout circuit, as compared to the situation in ref . Hence, the design of the readout scheme can emphasize more on the optimization of parameters such as the amplification of the voltage signal, rather than be limited by the short readout time.…”
Section: Discussionmentioning
confidence: 99%
“…τ 5 is related to the electron transit time and is negligibly short for a small QD and a thin barrier layer; τ 6 is essentially the hole lifetime, and can be estimated with 1/Γ hs . Since Γ hs is usually small for thick barriers, τ 6 is relatively long and can be of the order of microsecond or even longer. , This long lifetime translates into a long retention time for Δ V sp6 , which helps relax the stringent requirements imposed on the timing and the speed of the measurement electronics connected to the sense probe. To speed up the reset process, a positive pulse can be applied to the gate to eliminate Δ V sp6 (yellow dashed line in Figure f) and hence bring the detector back to the initial state shown in Figure a.…”
Section: Working Modes Of the Proposed Sqdspdmentioning
confidence: 99%
“…A tightly packed array of tiny islands, each around 15 nm across, could store 1 terabyte (1,000 GB) of data per square inch, the researchers say. Dieter Bimberg and colleagues at the Technical University of Berlin, Germany, with collaborators at Istanbul University, Turkey, demonstrated that it is possible to write information to the quantum dots in just 6 ns [ 165 , 166 ]. The key advantages of quantum dot (QD) NVMs are the high read/write speed, small size, low operating voltage, and, most importantly, multibit storage per device.…”
Section: Reviewmentioning
confidence: 99%
“…Semiconductor quantum dots (QDs) have become more and more fascinating nanoscopic structures due to their increasing demand in information storage in non-volatile memory (NVM) applications. [1][2][3] NVM devices are used as a main component in all types of portable electronic gadgets such as solid state disks, smart phones, tablet PCs, etc. Most of the commercially available memory devices consist of a metal-oxide-semiconductor (MOS) structure.…”
Section: Introductionmentioning
confidence: 99%